Effect of Fuzzy Logic Controller Implementation on a Digitally Controlled Robot Movement - Soh, Azura Che; Alwi, rny Aznida; Rahman, Ribhan Zafira Abdul; Fey, Li Hong (Kathmandu University Journal of Science Engineering and Technology, 2008)
Advanced intelligent control design cannot entirely replace the application of conventional controller in robotic system. On the other hand, intelligent controllers can be implemented into conventional controller design to increase its performance and ability. Most of intelligent control in movement control involves fuzzy logic and neural network system. This study features the influence of fuzzy logic controller upon the performance of robot movement simulation, which is controlled by a digital controller. Model design and simulation are done in SIMULINK, using Fuzzy Logic Toolbox provided by MATLAB software to control the movement speed of a robotic designed system. Finally, the movement speed is found better off controlled with the additional of fuzzy logic controller instead of the digital controller solely. Keywords: Intelligent Control; Fuzzy Logic; Digital Controller; Robot Movement; Simulink. DOI: 10.3126/kuset.v4i1.2881 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 28-39